Application of organic fertilizers in yield and root development in avocado cultivation - Campos Mariscal, José Luis; Álvarez Sánchez, María Edna; Maldonado Torres, Ranferi; Vargas Gustavo, Almaguer (Revista Mexicana de Ciencias Agrícolas, 2020)
Mexico is a world leader in the avocado market, participates with a production of 2 029 886 tons that represents 34.3% of the world volume produced, placing it in the first exported with 45.95% and with the highest per-capita consumption, with 10 kg per year). The yields per hectare are 10.1 t ha-1, which place it in fourth place worldwide (SAGARPA, 2017). The effect of a more leached compost of earthworm humus plus chemical fertilization on the root development and avocado yield was evaluated. In the experiment 3 levels of compost were applied: 100, 150 and 200 kg tree, accompanied by a conventional chemical fertilization proposed based on the nutrient diagnosis of the soil, which was 2 kg of the formula 20-10-05 per tree, plus 1.5 L of leachate in 60 L of water for each tree, equivalent to 300 L ha-1 per cycle. The control treatment consisted of a dose of only 2 kg per tree of the conventional formula 20-10-05 applied by the producer without the supply of organic fertilizers. The results indicated that the soil had a deficient level of Mn, low levels of N, Fe, Zn and B, an average level of Cu, while K and Ca were at high levels and N and Mg in excess. The superficial root development responded favorably to the treatments with application of organic fertilizers and had a direct correlation (p≤ 0.05) with the yield, as well as with the nutrient concentrations of Mg, Fe, Zn, Cu, B and organic matter obtained from sampling of soil of each treatment
Keywords: compost; fertilization; nutritional requirements